2007
DOI: 10.1021/jp0736692
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Electron Cascade Dynamics in KI and CsI

Abstract: We present a study of the characteristics of secondary electron cascades in two photocathode materials, KI and CsI. To do so, we have employed a model that enables us to explicitly follow the electron trajectories once the dielectric properties have been derived semiempirically from the energy loss function. Furthermore, we introduce a modification to the model by which the energy loss function is calculated in a first-principle manner using the GW approximation for the self-energy of the electrons. We find go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
(100 reference statements)
1
10
0
Order By: Relevance
“…[9][10][11] In the near future, hard X-ray sources like X-ray free electron lasers (XFEL), such as the Linac coherent light source (LCLS) 12 in Menlo Park, California and the European XFEL 13 in Hamburg, as well as table-top XFELs, [14][15][16][17][18] will provide X-ray pulses that allow imaging of single molecules 19 or even entire living cells 20 at, or near, atomic resolution. Due to the severe radiation damage by photo ionizations 19,21,22 and subsequent impact ionizations [23][24][25][26] induced by the intense X-ray pulses, every sample will diffract only once. To get enough useful signal scattered onto the detector, samples must be delivered into the X-ray beam in a repetitive and reliable manner; 27 ESI methods have proven to be capable of just that.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] In the near future, hard X-ray sources like X-ray free electron lasers (XFEL), such as the Linac coherent light source (LCLS) 12 in Menlo Park, California and the European XFEL 13 in Hamburg, as well as table-top XFELs, [14][15][16][17][18] will provide X-ray pulses that allow imaging of single molecules 19 or even entire living cells 20 at, or near, atomic resolution. Due to the severe radiation damage by photo ionizations 19,21,22 and subsequent impact ionizations [23][24][25][26] induced by the intense X-ray pulses, every sample will diffract only once. To get enough useful signal scattered onto the detector, samples must be delivered into the X-ray beam in a repetitive and reliable manner; 27 ESI methods have proven to be capable of just that.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, urea crystals are a good model for protein nanocrystals, known to contain 30%-60% water. We refer to [5,9,16] and the supplementary material for further details of these calculations and how the model compares with experiments on diamond [17]. Considering m i to be the mass of electron i and r i the position of electron i with respect to the center of mass of all free electrons, the radius of gyration, used in Figure 2, is defined as…”
mentioning
confidence: 99%
“…Non-thermal melting can be caused by absorption of multiple photons from, for instance, a Ti : sapphire laser, which leads to direct as well as indirect ionization processes (through secondary electron cascades [19][20][21][22][23][24][25]. Quite a few studies of the different mechanisms leading to thermal and non-thermal melting of silicon and other semiconductors have been presented recently, [26][27][28][29][30][31] and similar studies for metals have been reported as well.…”
Section: Introductionmentioning
confidence: 92%